Annular Elastolytic Giant Cell Granuloma: A Rare Case Report - Mansi Agarwal; Shruti Sharma; Prashant Verma; Paridhi Singh (Indian Journal of Dermatopathology and Diagnostic Dermatology)
Annular elastolytic giant cell granuloma (AEGCG) falls under the category of elastolytic granulomas. The histologic findings of a granulomatous dermatitis with loss of elastic fibres and elastophagocytosis are characteristic of AEGCG. It is a rare lesion and only a few cases have been documented. It predominantly affects males and typically manifests in individuals during their fourth to seventh decades of life. Clinically, it presents in the sun-exposed areas of the face, neck, arms, and upper back with papules and erythematous or skin-colored annular plaques having raised erythematous borders. We report the case of a 27-year-old male who came to the dermatology outpatient department with a chronic history of multiple skin-colored papules spread over his chest, back, and extremities. Histopathology was diagnostic of AEGCG.